An Epidemiological Cross-Sectional Comparative Study of Nutritional Status between Government and Private Primary School Children of Meerut City, Uttar Pradesh - Shruti Sehgal; Rama Shankar; Jay Vir Singh; Tauseef Alvi; Sangeeta Jain (Medsci Publications, 2017)
Background: School age recognized to be active growing phase of life. Study of ecology of malnutrition along with nutritional assessment is to map out the geographical distribution of malnutrition. The present study with regard to assessment of the nutritional status of children of both government and private primary schools of Meerut city was done. Objectives: 1.To assess the malnutrition status in primary school of government & private school of Meerut city. 2 Comparison of malnutrition status between government and private primary schools of Meerut City. Methodology: Between the period of May 2016-November 2016, a cross sectional study was conducted in one of the primary school of private and government schools. With the help of multistage stratified random sampling initially two separate strata of schools made (private and government). From enlisted schools one government and private school was selected randomly from each list. Results: The prevalence of underweight, and overweight among private school children of Meerut city was 138 (19.4%) and 152 (21.6%) and of government primary school of Meerut city was 140 (28%) and 96 (19%) respectively. Children of both school on vegetarian diet showed more prevalence of underweight (32.4% and 23.2%) than on mixed diet and this was significant.